The link between childhood neighborhood context and substance use disorder symptoms at age 39: The role of socioeconomic status at age 30 - Lee, Jungeun Olivia (Public Health, 2018)
OBJECTIVES: To examine whether (a) childhood neighborhood context predicts alcohol use disorder, nicotine dependence, and cannabis use disorder symptoms at age 39 and (b) socioeconomic status during young adulthood mediates these relationships. Gender differences were also examined. STUDY DESIGN: Seattle Social Development Project, a prospective longitudinal study of 808 individuals followed from ages 10 to 39 in Seattle, Washington, United States. The sample was gender balanced (51% male). METHODS: Alcohol, nicotine, and cannabis use disorder symptoms were assessed using the DSM-IV-based Diagnostic Interview Schedule. Childhood neighborhood data consisted of 10 neighborhood-level variables from the 1990 national census, which were consolidated using principal component analyses. Two components with eigenvalues greater than 1 were extracted—neighborhood disadvantage and neighborhood stability. Educational attainment and employment status represented socioeconomic status during young adulthood. Covariates included baseline symptoms of psychopathology, baseline substance use, gender, ethnicity, and childhood socioeconomic status at the family level. Negative binomial regression was used as the primary modeling strategy. Six models for each outcome measure were estimated. The first three models examined associations between two neighborhood components and each substance use outcome measure. Next, we tested the second research question by adding unemployment and college graduate indicators at age 30 as potential mediators underlying the link between childhood neighborhood context and three substance use measures. RESULTS: Study findings revealed that childhood neighborhood stability significantly reduced alcohol and cannabis use disorder symptoms nearly 3 decades later. Path analyses suggested that socioeconomic status during the transition to adulthood did not influence these relationships, but rather had independent effects on problematic nicotine and cannabis use. Furthermore, the effects of childhood neighborhood factors on problematic nicotine use were stronger for men. CONCLUSIONS: Neighborhood characteristics during childhood may be important factors for alcohol and cannabis use disorder symptoms among adults and nicotine dependence disorder symptoms among men. Prevention efforts that address community stability and disadvantage can and should start in childhood, with a focus on intervention targets that might gain salience later in life to discourage the development and persistence of problematic substance use in adulthood.